2018
DOI: 10.18632/aging.101728
|View full text |Cite
|
Sign up to set email alerts
|

A klotho gene single nucleotide polymorphism is associated with the onset of stroke and plasma klotho concentration

Abstract: Klotho protects against development of multiple age-related disorders, including cardiovascular diseases. We assessed whether a human klotho single nucleotide polymorphism (SNP) rs650439 is associated with the onset of stroke in hypertensive patients and plasma klotho concentration in the general population. Five hundred and twenty-three patients with hypertension were analyzed for both the presence of rs650439 and onset of stroke. We found that hypertensive patients with the TT genotype of rs650439 (n=52) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(42 reference statements)
0
6
0
2
Order By: Relevance
“…A growing body of evidence has suggested that some single nucleotide polymorphisms in the klotho gene were correlated with the circulating klotho levels and the susceptibility to hypertension 24 , salt hypertension 8 , and coronary artery disease 25 as well as the onset of stroke 26 . Though we did not find a significant relationship between the serum klotho concentrations, blood pressure, and PWV, we cannot exclude the possibility that genetic polymorphisms of the klotho gene may be associated with blood pressure and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has suggested that some single nucleotide polymorphisms in the klotho gene were correlated with the circulating klotho levels and the susceptibility to hypertension 24 , salt hypertension 8 , and coronary artery disease 25 as well as the onset of stroke 26 . Though we did not find a significant relationship between the serum klotho concentrations, blood pressure, and PWV, we cannot exclude the possibility that genetic polymorphisms of the klotho gene may be associated with blood pressure and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…46 For instance, another intronic variant in KL rs650439 was suggested to be associated with plasma Klotho concentration. 47 In addition, previous large eQTL meta-analysis in whole blood suggested the SNP rs495392 as cis-eQTL signal for the expression of KL gene. 17 Although the present study does not have the information on serum Klotho concentrations, the expression of sKL in liver tissues was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Dado el papel de los fgf endocrinos en un rango de respuestas fisiológicas, incluidos minerales y energía metabólica, respuestas al estrés y trastornos relacionados con el envejecimiento, agonistas y antagonistas de estas hormonas son posibles candidatos terapéuticos para diversos trastornos (19,20). Los datos estructurales obtenidos para endocrina espera que los fgf y las proteínas Klotho se aceleren (21,22,23).…”
Section: Discussionunclassified
“…βKlotho ha sido cristalizado con y sin fgf21. De manera similar a la interacción de αKlotho con fgf23, βKlotho interactúa directamente con el término c de fgf21 (5,(15)(16)(17)(18); sin embargo, no se pudo resolver la estructura de algunas regiones de este complejo, incluida la rba de αKlotho (19)(20)(21)(22)(23).…”
Section: Factor De Crecimiento De Fibroblastos (Fgf)unclassified